2011
DOI: 10.1371/journal.pmed.1000435
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Adrenaline, Promethazine, and Hydrocortisone in the Prevention of Acute Adverse Reactions to Antivenom following Snakebite: A Randomised, Double-Blind, Placebo-Controlled Trial

Abstract: In a factorial randomized trial conducted in Sri Lanka, de Silva and colleagues evaluate the safety and efficacy of pretreatments intended to reduce the risk of serious reactions to antivenom following snakebite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
134
3
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 21 publications
1
134
3
3
Order By: Relevance
“…With adrenaline, the balance of benefit over harm when given prophylactically varies with the baseline risk of developing the adverse reactions. Prophylactic use of subcutaneous adrenaline appears safe, as no serious adverse events were reported by de Silva et al [3] or in previous studies [14,15]. Adverse reaction rates have been known to vary between different brands of antivenom due to different manufacturers' procedural differences and between different batches of the same brand of antivenom due to production process variability.…”
Section: Leading Articlementioning
confidence: 75%
See 3 more Smart Citations
“…With adrenaline, the balance of benefit over harm when given prophylactically varies with the baseline risk of developing the adverse reactions. Prophylactic use of subcutaneous adrenaline appears safe, as no serious adverse events were reported by de Silva et al [3] or in previous studies [14,15]. Adverse reaction rates have been known to vary between different brands of antivenom due to different manufacturers' procedural differences and between different batches of the same brand of antivenom due to production process variability.…”
Section: Leading Articlementioning
confidence: 75%
“…However, the study was small (105 patients) and could not firmly establish the safety of adrenaline. Recently, de Silva et al [3], in a study of 1007 patients who received antivenoms currently being used in Sri Lanka, reports that using low-dose subcutaneous adrenaline (0.25 ml, 1:1000 solution) for prophylaxis is both effective and safe, and recommends its use especially in countries where adverse reactions to antivenoms are frequent. Adrenaline reduced the rate of severe adverse reactions compared with placebo by 43% at 1 hour (OR 0.57, 95% CI 0.43-0.75) and by 38% over 48 hours (OR 0.62, 0.51-0.74).…”
Section: Leading Articlementioning
confidence: 99%
See 2 more Smart Citations
“…14 17 However steroids have been used post ASV to prevent serum sickness in Australia. 18 Studies by williams et al had shown adrenaline to be effective.…”
Section: Discussionmentioning
confidence: 99%